JIN SEON’S DEFENSE MECHANISM IN CARNBY KIM AND YOUNGCHAN HWANG’S BASTARD - Yuliastuti, Anicleta; Putri, Braga Permata (Faculty of Letters, Dr. Soetomo University, 2018)
The thesis writer focuses on the analysis of Jin Seon?s defense mechanism as seen in Carnby Kim and Youngchan Hwang?s Bastard. The topic defense mechanism is chosen because it is important to find out of the proofs, the causal factors, and the effects of defense mechanism of the main character. There are three objectives intend to be achieved in this thesis, they are; to find out the proofs of Jin Seon?s defense mechanism, the causal factors of Jin Seon?s defense mechanism, and the effects of Jin Seon?s defense mechanism on himself, on Kyun Yoon, and on his father. The thesis writer applies the theory of defense mechanism, the concept of defense mechanism as seen in psychological point of view by Sigmund Freud, and conducts a descriptive qualitative research. The finding shows that there are fifteen proofs of Jin Seon?s defense mechanism and it is divided into four proofs for denial, three proofs for repression, two proofs for projection, one proof for reaction formation, three proofs for rationalization, and two proofs for sublimation. Besides, the thesis writer also concludes that there are ten causal factors of Jin Seon?s defense mechanism that are: two denial causal factors, one repression causal factor, two projection causal factor, one reaction formation causal factor, two rationalization causal factor, two sublimation causal factor. While both of them, the thesis writer also conclude that there are effects of Jin Seon?s defense mechanism on himself, on Kyun Yoon, and on his dad.Keywords:Defense, Mechanism, Webtoon.